2009
DOI: 10.1097/brs.0b013e3181973e35
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Improved Outcomes With a Less Invasive Posterior Lumbar Interbody Fusion Incorporating Total Facetectomy

Abstract: Clinical outcomes were significantly improved after both ST-PLIF and LI-PLIF. However, outcomes were significantly better after LI-PLIF than after ST-PLIF. Significantly shortened hospital stay with LI-PLIF probably reflected the "less invasive" technique per se. Significantly better clinical outcomes with fewer complications after LI-PLIF, however, potentially reflected maneuvers singular to LI-PLIF: (1) preservation of posterior elements, (2) avoidance of far lateral dissection over the transverse processes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 22 publications
1
31
0
1
Order By: Relevance
“…Successful bone union was achieved in all the 18 patients at the final follow-up. The mean modified JOA score had improved from 7.7 (4-11) just prior to repeat PLIF to 11.4 (7)(8)(9)(10)(11)(12)(13)(14)(15) at the time of the maximum recovery and had slightly declined to 10.2 (5-13) at the final follow-up. The duration between repeat PLIF and the latest date of the maximum recovery was 30 (3-60) months.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Successful bone union was achieved in all the 18 patients at the final follow-up. The mean modified JOA score had improved from 7.7 (4-11) just prior to repeat PLIF to 11.4 (7)(8)(9)(10)(11)(12)(13)(14)(15) at the time of the maximum recovery and had slightly declined to 10.2 (5-13) at the final follow-up. The duration between repeat PLIF and the latest date of the maximum recovery was 30 (3-60) months.…”
Section: Resultsmentioning
confidence: 93%
“…Many authors have reported excellent clinical outcomes as well as high fusion rates after PLIF [10,11], indicating that PLIF is an appropriate procedure for treating an abnormal mobile segment. Although transforaminal lumbar interbody fusion (TLIF) is also reported to produce high fusion rate and excellent clinical outcomes [18,19], the additional fusion needs enough rigidity because of more stress by the longer lever arm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11][12] The current trend favours minimally invasive surgery (MIS) of the spine due to lower complication rates and approach-related morbidity with minimal soft tissue trauma, reduced intraoperative blood loss and risk of transfusion, improved cosmesis, decreased postoperative pain and narcotic usage, shorter hospital stays, earlier mobilisation with faster return to work and thus reduced overall health care costs. 1,4,[6][7][8][9][13][14][15][16][17][18] However, to our knowledge there is no quality published articles showing that MIS is superior to open spinal surgery. The aim of this study was to directly compare the effectiveness of MIS to conventional open spinal fusion, by assessing clinical outcomes and patient satisfaction.…”
Section: Introductionmentioning
confidence: 73%
“…These were confirmed by dynamic radiographs, CT scans and MRI. The average follow-up time following MIS procedures was approximately 11.5 months (range: 5.40-20.10 months) in comparison to 18 Table, Orthopedic Systems, Union City, CA, USA) was used. A posterior lumbar interbody fusion (PLIF) graft was inserted via a small (3-5 cm) midline incision over the disc space to be fused (Fig.…”
Section: Patientsmentioning
confidence: 99%